Comparative analysis of bone healing in subcritical defects with air turbine and electric handpiece in a rat model. - Izabella Sol; Henrique Hadad; Tatsuya Henrique Kano; Karen Rawen Tonini; Martina Andreia Lage Nunes; Daniela Ponzoni (PLoS ONE)
Rotatory devices are essential in clinical surgical practice, however, depending on the different systems available, their function can impact bone repair and postoperative responses on varying scales. This impact underscores the need to explore new techniques aiming to enhance bone repair. This study aimed to assess the immediate and delayed effects on bone healing in subcritical bone defects using both air turbine and an electric handpiece. For this purpose, 40 male Wistar rats were allocated into two groups. The Control Group (CG) had bone defect made using an air turbine device, while the Experimental Group (EG) had defects made using an electric handpiece. Ten animals were sacrificed for each time of evaluation. Bone neoformation, microstructure, and collagen organization were assessed ate 7, 15 and 30 days postoperative. Inflammatory profiling was conducted at 7 and 15 days. Immediate thermal osteonecrosis were evaluated after the use of rotary systems. Multivariate analysis was used to access statistical differences. The EG exhibited enhanced parameters of bone neoformation in all analyses, with statistical difference between 15 and 30 days (P = .0002) and in comparison with CG in 30 days (P = .0009). A reduced number of inflammatory cells and increased angiogenesis in the initial periods was seen in EG, corroborating the consistent values of collagen type 1 and a decrease of collagen type 3 over times. Immediate thermal osteonecrosis was statistically higher for the CG (P < .05), which showed adequate neoformation of subcritical defects but consistently lower values than those found in the EG. These data suggest that the electric handpiece demonstrated more bone repair area, proving to be an excellent alternative to surgical practice.